Pengaruh Bukti Sosial dan Kepercayaan Online terhadap Keputusan Pembelian pada Konsumen Marketplace - Agnes Zulyatika; Chairunnisa Nur Rafah; Isra Rafika Sihombing (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
The digital era has driven rapid growth in electronic commerce in Indonesia, particularly through marketplace platforms such as Shopee, Tokopedia, and TikTok Shop. Consumers often face uncertainty because they cannot physically inspect products, making social proof (in the form of reviews, ratings, testimonials, and recommendations) and online trust crucial factors influencing purchasing decisions. This study aims to analyze the influence of social proof and online trust on consumer purchasing decisions in marketplaces using a qualitative approach based on library research (literature review). Previous or relevant research is essential in any study or scientific article, as it strengthens the theoretical foundation and the phenomenon of the relationships or influences between variables. This article reviews the factors influencing social proof and online trust on purchasing decisions through a marketing management literature study. The purpose of this marketing management literature review article is to develop hypotheses that can be used in future research. The results of this library research indicate: 1) The influence of social proof on purchasing decisions; 2) The influence of online trust on purchasing decisions; 3) The simultaneous influence of social proof and online trust on purchasing decisions; and 4) Theoretical and practical implications.